Multi‐constrained QoS routing based on PSO for named data networking. Issue 8 (31st May 2017) - Hou, Rui; Chang, Yuzhou; Yang, Liuqing
Abstract : Named data networking (NDN) is a representation and implementation of an information centric network, which is considered as one of the next generation of network architectures. To the best of the authors' knowledge, very few studies have considered multiple constrained quality‐of‐service (QoS) routing in NDN. In this study, a particle swarm optimisation‐forwarding information base (PSO‐FIB) algorithm that uses the forwarding experiences of particles to maintain the forwarding probability of each entry in the FIB is proposed. Illustrating the interaction of PSO‐FIB with the routing layer, the simulation results show that PSO‐FIB can support multi‐constrained QoS routing and achieve better performance in terms of successful delivery rate and average cost compared with random and ant colony optimisation strategies.